25. THE STATUS OF STRESS AMONG HEALTHCARE STAFF AT THANH BA DISTRICT HEALTH CENTER, PHU THO PROVINCE IN 2024, AND SOME ASSOCIATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current stress status of medical staff and some associated factors at Thanh Ba District Medical Center in 2024.Subjects and methods: A cross-sectional interview design was conducted with 173 healthcare staff, utilizing the DASS-21 scale to assess stress levels and univariate logistic regression to analyze associations.Results: Among the 173 medical staff, the stress prevalence was 19.2%. Of these, mild stress accounted for 51.5%, moderate stress for 27.3%, and severe stress for 21.2%. There was a statistically significant difference in stress levels between doctors and nurses, technicians/pharmacists (p
Keywords: Stress; DASS-21; Thanh Ba District Medical Center